Novel mediator in anaphylaxis: decreased levels of miR-375-3p in serum and within extracellular vesicles of patients - Nuñez-Borque, Emilio; Fernandez-Bravo, Sergio; Rodríguez Del Rio, Pablo; Palacio-García, Lucia; Di Giannatale, Angela; Di Paolo, Virginia; Galardi, Angela; Colletti, Marta; Pascucci, Luisa; Tome-Amat, Jaime; Cuesta-Herranz, Javier; Ibañez-Sandin, María Dolores; et al. (Frontiers in Immunology, 2023)
Anaphylaxis is among the most severe manifestations of allergic disorders, but its molecular basis remains largely unknown and reliable diagnostic markers are not currently available. MicroRNAs (miRNAs) regulate several pathophysiological processes and have been proposed as non-invasive biomarkers. Therefore, this study aims to evaluate their involvement in anaphylactic reaction and their value as biomarkers. For this purpose, acute (anaphylaxis) and baseline (control) serum samples from 67 patients with anaphylaxis were studied. Among them, 35 were adults with drug-induced anaphylaxis, 13 adults with food-induced anaphylaxis and 19 children with food-induced anaphylaxis. The circulating serum miRNAs profile was characterized by next-generation sequencing (NGS). For this purpose, acute and baseline samples from 5 adults with drug-induced anaphylaxis were used. RNA was extracted, retrotranscribed, sequenced and the readings obtained were mapped to the human database miRBase_20. A total of 334 miRNAs were identified, of which 21 were significant differentially expressed between both phases. Extracellular vesicles (EVs) were characterized by Western blot, electron microscopy and NanoSight. A decrease of miR-375-3p levels was determined by qPCR in both serum and EVs of patients with anaphylaxis (****p<.0001). In addition, a system biology analysis (SBA) was performed with its target genes and revealed pathways related to anaphylactic mediators signaling. Precisely, the decrease of miR-375-3p correlated with the increase of two inflammatory cytokines: monocyte chemoattractant protein-1 (MCP-1) and granulocyte macrophage colony-stimulating factor (GM-CSF). On the other hand, functional and molecular endothelial permeability assays wereconducted with miR-375-3p-transfected cells in response to cAMP. Data obtained showed that this miRNA partially blocked the endothelial barrier maintenance and stabilization by disassembly of cell-cell junctions exhibiting low Rac1-Cdc42 levels. These findings demonstrate a differential serum profile of circulating miRNAs in patients with anaphylaxis and exhibit the miR-375-3p modulation in serum and EVs during drug- and food-mediated anaphylactic reactions. Furthermore, the in silico and in vitro studies show a negative role for miR-375-3p/Rac1-Cdc42 in the endothelial barrier stability.